An interview with Steven J. Lindauer - Steven J. Lindauer
There are so many compliments to Dr. Steven Lindauer that is hard for one to figure where to start from... Well, travelling backwards in time, all the way to the year 2000, I went to Virginia to study English at Virginia Commonwealth University (VCU), in Richmond, Virginia, USA. During my daily walks to the English school, I used to pass by the School of Dentistry, where the Department of Orthodontics was. That was the place where my very first "contact" with the VCU happened. In 2015, 15 years later, I had the pleasure to go back to the VCU and spend two days with Dr. Steven Lindauer. I have to confess that I was anxious and nervous to get to know not only the Chair of the Department, but also the Editor-in-chief of "The Angle Orthodontist". Since the very first moment I could experience how incredibly positive and pro-active the environment within the Department was. Staff members, Residents and Faculty members used to work very gladly and in perfect synergy. After a quick chat with the residents, I heard from them: "Dr. Lindauer is an unprecedented human being! Besides a brilliant Professor, Researcher and Administrator, he is like a father to all of us!" Besides this touching testimony, I also heard flattering compliments from workmates to the great friend, leader and partner Dr. Lindauer was. Here goes some food for thought, though. Unfortunately, the leader is often compelled to resort to unpopular measures in order to enforce compliance. Dr Lindauer is the living proof that a boss, a leader, can be a light, humble, friendly and highly charismatic human being. In 2016, I was given a second chance to enjoy Dr. Lindauer's company when he visited Brazil as a guest lecturer in Salvador, at the Federal University of Bahia and the Brazilian Association of Orthodontics (Bahia Chapter). I noticed, once again, that besides an excellent lecturer and careful clinician, he mastered orthodontic mechanics very proficiently. And needless to say at length about his brilliance ahead of "The Angle Orthodontist"... It didn't take me long to realize that his virtues by far exceeded the boundaries of the professional domain. Despite his utterly busy schedule, he is still able to dedicate time to his parents, taking them to trips around the world. Interestingly, at every international trip, he always remembers his puppies (Memphis, Baxter and Kingston - in memoriam), taking sightseeing pictures to immediately Photoshop them into. Having done the well deserved introductions to our distinguished interviewee, I would like to offer righteous acknowledgements to the colleagues Jorge Faber, David Turpin, Bhavna Shroff and David Normando, for having accepted the invitation to take part in this interview. I also would like to offer my heartfelt thanks to Dental Press for having entrusted me with the honor to conduct this project. I wish all readers as delightful and rich of an experience when going through this interview as it's been the scientific path that brought us all here in the first place. No doubts, you stand in face of a life dedicated to Orthodontics. (Andre Wilson Machado, interview coordinator)